2022
DOI: 10.4103/sjg.sjg_547_21
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal manifestations of COVID-19 in a single center in the Eastern Province of Saudi Arabia

Abstract: Background: Several gastrointestinal (GI) symptoms have been associated with novel coronavirus disease-2019 (COVID-19). Their prevalence and relation to the severity and hospital outcome of COVID-19 have not been well reported in the Middle East and Saudi Arabia. We aimed to examine the GI manifestations of COVID-19 and their association with the severity and hospital outcome of COVID-19 infection. Methods: We conducted a retrospective observational study of hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Among GI complaints, diarrhea was the most common complaint that was reported in 40.6% of our patients, followed by nausea/vomiting in 40%. Similar findings have been reported in different parts of the world by different investigators 19,20,23–25 . However, a meta‐analysis conducted by Dong et al 20 reported anorexia at 17% as the most common symptom in COVID‐19 patients, followed by diarrhea at 8%, nausea, and vomiting at 7%, and abdominal pain at 3%.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Among GI complaints, diarrhea was the most common complaint that was reported in 40.6% of our patients, followed by nausea/vomiting in 40%. Similar findings have been reported in different parts of the world by different investigators 19,20,23–25 . However, a meta‐analysis conducted by Dong et al 20 reported anorexia at 17% as the most common symptom in COVID‐19 patients, followed by diarrhea at 8%, nausea, and vomiting at 7%, and abdominal pain at 3%.…”
Section: Discussionsupporting
confidence: 79%
“… 17 , 18 , 19 , 20 , 21 , 22 However, many studies reported GI symptoms in less than 30% of patients infected with COVID‐19, ranging from 12.1% to 29.9%. 23 , 24 , 25 , 26 , 27 , 28 , 29 A higher prevalence of GI symptoms could be due to the tendency to admit as many RT‐PCR‐positive patients as possible in our study center to isolate and prevent the spread of infection during the study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of GI complications in our study was 35.23%. Many of the previously conducted studies have shown varying results such as in a Saudi study conducted by Al Argan RJ et al 15 has shown that GI manifestation accounts for 28.5%, and a meta-analysis conducted by Merola E and colleagues, 16 has observed that GI manifestations were the most common clinical manifestations and accounts for 11.51%, in another study conducted at Iraq by Sulaiman T and colleagues, 17 had observed lower prevalence of GI manifestation which accounts for 23.6% of the patients admitted with COVID-19. While, study from Southern US has shown higher prevalence of GI manifestations (40.7%) among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%